Raça e nação em disputa : Instituto Luso-Brasileiro de Alta Cultura, 1ª Exposição Colonial Portuguesa e o 1º Congresso Afro-Brasileiro (1934-1937) - Skolaude, Mateus Silva (2016)
This thesis rises from the coincidence of three scientific and political events that happened in 1934, which established intellectual relationships between Brazilian and Portuguese: The Luso-Brazilian Institute of High Culture, founded in June in Rio de Janeiro, the First Portuguese Colonial Exhibition, occurred during the months of June to September in the city of Porto and the First Afro- Brazilian Congress, held in November in Recife. Considering the intense flow of ideas and the exchange of Portuguese and Brazilian literates who were being constituted as scientific reference in different areas, the thesis addresses special interest to the configuration of intellectual networks articulated around the authors Mendes Correia and Gilberto Freyre in order to analyze the racial and national debates mobilized within the three studied events.